The Influence of Job Satisfaction, Distributive Justice and Affective Commitment to Organizational Citizenship Behavior (PKO) in Islamic Bank Employees in Indonesia - Febrian, Andis; Widianita, Rika; Putri, Zulvaruri Sintia (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: The purpose of this research is to identify and analyze the effect of job satisfaction and distributive justice on affective commitment, the effect of job satisfaction, distributive justice and affective commitment on organizational citizenship behavior, and to see the effect of job satisfaction and distributive justice on organizational citizenship behavior mediated by affective commitment. On Islamic bank employees in Indonesia.Design/Method/Approach: The research method used in this study is quantitative descriptive of Islamic bank employees in Indonesia. The total population in this study was 85 people from three Islamic banks in the Padang and Pekanbaru areas. The numbers of samples in this study were 70 people and the data used was primary data by distributing questionnaires to employees. The data collected in this study will be tested using research instrument tests, classical assumption tests, multiple regression tests, and hypothesis testing.Findings: The findings in this study are that there is a significant positive relationship between the effect of satisfaction and distributive justice on affective commitment, the effect of job satisfaction, distributive justice and affective commitment on organizational citizenship behavior, and the effect of job satisfaction on organizational citizenship behavior mediated by affective commitment in Islamic bank employees in Indonesia, and there is a non-significant relationship between the effect of distributive justice on organizational citizenship behavior mediated by affective commitment in Islamic bank employees in Indonesia.Originality/Value: The contribution of this research is to see how the citizenship behavior of employee organizations of Islamic banks in Indonesia can improve company performance so that they can compete with conventional banks